Generalised mathematical model to estimate Zn, Pb, Cd, Ni, Cu, Cr and As release from contaminated estuarine sediment using pH-static leaching tests. (22nd December 2015) - Martín-Torre, M.Camino; Ruiz, Gema; Galán, Berta; Viguri, Javier R.
Abstract: Variations in the environmental conditions in marine and estuarine environments can lead to the release of elements from the sediment to the seawater phase. The pH dependence leaching test with continuous pH-control evaluates the release of constituents as a function of the pH. In this work, analysis of the Zn, Pb, Cd, Ni, Cu, Cr and As release from marine sediment of the Suances estuary (northern Spain) is performed using a leaching test with continuous pH control at pH values of 4, 5, 5.5, 6, 6.5 and 7 with seawater as the leaching liquid. These pollutants present different experimental leaching patterns over time but not all of them are well fitted by the previous models. Hence, a generalised model of the different time-dependent releases under these conditions is proposed. The model considers three reactions in series: (i) the oxidation reaction of the reduced fraction to consider the speciation change over time, (ii) the metal release of the oxidised fraction to the bulk dissolution and (iii) the adsorption or precipitation after the element release. The maximum concentration of each pollutant that could be released from the reduced fraction and from the oxidised fraction and the rate coefficients are the parameters of the proposed model. The rate coefficients of the reactions for each pollutant fit well to a second order equation as a function of pH. Using the Aspen Custom Modeler software, the model parameters have been estimated. A good agreement between the experimental and modelled concentration values is obtained. In addition to improving upon the previous results from models with reactions in parallel, the proposed model predicts the metal mobility delay at short times for Zn, Pb, Cd and Cu and the adsorption or precipitation process after an initial rapid release (As and Cr) reasonably well. The model provides good results when applied to two sediments with different levels of oxidation. The obtained model parameters would be useful when predicting the release of the studied elements for cases in which polluted sediment is totally mixed with inorganic acid-acidified seawater under continuous pH control semibatch leaching tests. Graphical abstract: Highlights: Trace element time-dependent release based on first order series reactions. The model fits initial delay of Zn, Pb, Cd and Cu and adsorption of As and Cr. The model is valid when applied to sediments with different levels of oxidation. Prediction of time-dependent leaching behaviour in scenarios of acidification.